Yttrium-doped cobalt-based catalyst and preparation method and electro-catalysis application thereof
Through the development of mixed cobalt catalysts, the problem of high potential in the hydrogenation hydrogen hydrogen hydrogenation of hydrogenation is solved, the high -efficiency hydrolyzed response is achieved, and the cost of catalysts is reduced, which has good stability and reaction activity.
Patent Information
- Application Number
- CN202411470489.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-01-24
AI Technical Summary
In the existing water electrolysis hydrogen production technology, the overpotential of the oxygen evolution reaction is much higher than the theoretical decomposition voltage of water, which limits the efficiency of the water electrolysis process, and the scarcity and high cost of precious metal oxide catalysts limit their large-scale application.
The development of a mixed cobalt catalyst, which includes cobalt oxides and cobalt -doping cobalt oxides, is prepared through the electrical deposition method and high -temperature burn method to form a unique nanoplene arrays Position.
Through the mixing cobalt catalyst, it significantly reduces the excess potential of water decomposition current density, improves the efficiency of water decomposition, reduces the cost of catalyst, and has good stability and reaction activity.
Smart Images

Figure HDA0005094557580000011 
Figure HDA0005094557580000021 
Figure HDA0005094557580000031
Abstract
Description
Technical Field
[0001] The present application belongs to the field of electrochemical catalysis, and specifically relates to an yttrium-doped cobalt-based catalyst, a preparation method thereof, and electrocatalytic applications. Background Art
[0002] It is imperative to seek clean energy that can replace fossil fuels. Hydrogen is considered a high-quality alternative energy source in energy strategy. At present, there are three main ways to produce hydrogen in industry, namely steam methane reforming, coal gasification and water electrolysis. Among them, steam methane reforming and coal gasification account for more than 95% of the total hydrogen, while water electrolysis accounts for only 4% of the total hydrogen. Obviously, the current hydrogen production is still heavily dependent on fossil fuels. This method of hydrogen production goes against the original intention of using hydrogen to reduce air pollution and global warming.
[0003] Among the three main hydrogen production pathways mentioned above, water electrolysis is sustainable and environmentally friendly, its raw water is renewable, and the hydrogen production reaction can be driven by solar energy, wind energy or other renewable resources. The key to realizing this overall strategy is an efficient water electrolysis process and fuel cell technology. For water electrolysis, the overpotential of the oxygen evolution reaction is much higher than the theoretical decomposition voltage of water (1.23V), which becomes the main limiting process of water electrolysis hydrogen production technology. Therefore, the design and synthesis of efficient OER catalysts are the key to improving the energy efficiency of water electrolysis hydrogen production. To date, the most efficient OER catalysts are still precious metal oxides, whose scarcity and high cost severely limit their large-scale application. Therefore, it is imperative to find low-cost alternative materials that can effectively reduce the OER kinetic limitations and improve the efficiency of water decomposition. Summary of the invention
[0004] In view of the above problems in the prior art, the present application provides a yttrium-doped cobalt-based catalyst, a preparation method thereof, and electrocatalytic applications.
[0005] In a first aspect, the present application provides a yttrium-doped cobalt-based catalyst, which includes a substrate and a composite material supported on the substrate, wherein the composite material includes cobalt oxide and yttrium-doped cobalt oxide.
[0006] The doping of yttrium in the catalyst of the present application can accelerate the electron transport and mass transfer rate during the reaction, and the abundant surface edge active sites make it have good alkaline and acidic oxygen evolution catalytic performance.
[0007] In some embodiments, the molar content of the yttrium element is 1%-15%, for example, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 13%, 14% or any value therebetween, based on the total molar amount of cobalt oxide and yttrium-doped cobalt oxide. In some embodiments, the molar content of the yttrium element is 3%-10%. In some embodiments, the molar content of the yttrium element is 4%-8%.
[0008] In some embodiments, the cobalt oxide is cobalt trioxide, and the yttrium-doped cobalt oxide is yttrium-doped cobalt trioxide. In some embodiments, the doping is bulk doping and / or surface doping, preferably bulk doping.
[0009] In the present application, the morphology of the yttrium-doped cobalt tetroxide changes (from a nanoarray sheet with obvious edges to a nanoarray with obvious curved edges), but the physical phase does not change significantly and remains a spinel type.
[0010] In some embodiments, the composite material is a composite material composed of a plurality of nanosheets, the nanosheets comprising cobalt oxide and yttrium-doped cobalt oxide.
[0011] In some embodiments, the composite material has a "nanosheet array" morphology composed of a plurality of nanosheets.
[0012] The catalyst provided in the present application has a unique "nanosheet array" morphology assembled from nanosheets and a characteristic structure in which the surface morphology changes with the incorporation of yttrium. The large specific surface area ensures electron transport and mass transfer diffusion, and the nanoarray assembled from two-dimensional nanosheets provides abundant reaction active sites. These factors enable the present application to have excellent electrocatalytic water decomposition performance.
[0013] In some embodiments, the loading amount of the composite material on the substrate is 0.3 mg / cm 2 -2.5mg / cm 2 , for example 0.4 mg / cm 2 , 0.5mg / cm 2 , 0.6mg / cm 2 , 0.7mg / cm 2 , 0.8mg / cm 2 , 0.9mg / cm 2 , 1.0mg / cm 2 , 1.1mg / cm 2 , 1.2mg / cm 2 , 1.3mg / cm2 , 1.4mg / cm 2 , 1.5mg / cm 2 , 1.7mg / cm 2 , 2.0mg / cm 2 , 2.2mg / cm 2 , 2.4mg / cm 2 Or any value therebetween. In some embodiments, the loading amount of the composite material on the substrate is 0.5 mg / cm 2 -1.5mg / cm 2 In some embodiments, the loading amount of the composite material on the substrate is 0.5 mg / cm 2 -1.0mg / cm 2 .
[0014] In some embodiments, the loading amount of the composite material on the substrate is 0.5 mg / cm 2 -0.7mg / cm 2 , preferably 0.6 mg / cm 2 -0.65mg / cm 2 More preferably 0.63 mg / cm 2 .
[0015] In some embodiments, the substrate is selected from one or more of conductive substrates. In some embodiments, the substrate is selected from one or more of carbon cloth, graphite sheet, nickel mesh and nickel foam.
[0016] In some embodiments, the carbon cloth is a conductive substrate woven from carbon fibers.
[0017] In a second aspect, the present application provides a method for preparing a yttrium-doped cobalt-based catalyst, which comprises the following steps:
[0018] S1: immersing the substrate in a solution containing a yttrium source and a cobalt source for electrochemical deposition to obtain a precursor containing cobalt oxyhydroxide;
[0019] S2: heat-treating the precursor of step S1 to obtain the yttrium-doped cobalt-based catalyst.
[0020] In some embodiments, the molar ratio of the yttrium source to the cobalt source is 1:5-1:50, for example, 1:7, 1:10, 1:11, 1:12, 1:13, 1:14, 1:15, 1:16, 1:17, 1:18, 1:19, 1:20, 1:21, 1:22, 1:23, 1:24, 1:25, 1:26, 1:27, 1:28, 1:29, 1:30, 1:33, 1:35, 1:37, 1:40, 1:43, 1:45, 1:47 or any value therebetween. In some embodiments, the molar ratio of the yttrium source to the cobalt source is 1:10-1:30. In some embodiments, the molar ratio of the yttrium source to the cobalt source is 1:15-1:25. In some embodiments, the molar ratio of the yttrium source to the cobalt source is 1:18-1:22.
[0021] In some embodiments, in step S1, the potential of the electrochemical deposition is -0.4V to -1.6V, for example, -0.5V, -0.6V, -0.7V, -0.8V, -0.9V, -1.0V, -1.1V, -1.2V, -1.3V, -1.4V, -1.5V or any value therebetween. In some embodiments, the potential of the electrochemical deposition is -0.8V to -1.2V.
[0022] In some embodiments, in step S1, the electrochemical deposition time is 5 min-60 min, for example, 10 min, 15 min, 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min or any value therebetween. In some embodiments, in step S1, the electrochemical deposition time is 10 min-40 min.
[0023] In some embodiments, the method further comprises repeating step S1 at least 5 times, for example 10 times, 15 times, 20 times or 25 times, to obtain a precursor comprising cobalt oxyhydroxide.
[0024] In some embodiments, in step S2, the temperature of the heat treatment is 200°C-500°C, for example, 250°C, 300°C, 350°C, 400°C or 450°C. In some embodiments, the temperature of the heat treatment is 300°C-500°C.
[0025] In some embodiments, in step S2, the heat treatment time is 0.5h-5h, for example, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h or 4.5h. In some embodiments, the heat treatment time is 1h-3h.
[0026] In some embodiments, the yttrium source is selected from one or more of soluble yttrium salts. In some embodiments, the yttrium source is selected from one or more of yttrium nitrate, yttrium sulfate, yttrium acetate and yttrium chloride.
[0027] In some embodiments, the cobalt source is selected from one or more of soluble cobalt salts. In some embodiments, the cobalt source is selected from one or more of cobalt nitrate, cobalt sulfate, cobalt acetate and cobalt chloride.
[0028] In some embodiments, the substrate is selected from one or more of conductive substrates. In some embodiments, the substrate is selected from one or more of carbon cloth, graphite sheet, nickel mesh and nickel foam.
[0029] In some embodiments, the method for preparing the yttrium-doped cobalt-based catalyst comprises the following specific steps:
[0030] Step 1: ultrasonically clean the surface attachments of the cut carbon cloth with a large amount of ultrapure water and ethanol, and then hydrophilize the carbon cloth after decontamination treatment with sulfuric acid and hydrogen peroxide.
[0031] Step 2: clamp the hydrophilic treated carbon cloth on the platinum electrode clamp and immerse it in a cobalt salt aqueous solution as the working electrode, the platinum electrode sheet as the counter electrode, and Ag / AgCl as the reference electrode. Use a workstation to apply voltage to the working electrode for electrodeposition. After completion, carefully rinse the carbon cloth material with deionized water and ethanol and dry it.
[0032] Step 3, the dried carbon obtained in step 2 is placed in a magnetic boat, loaded into a high-temperature box furnace, heated to 200°C-500°C, maintained for 2 hours, and then cooled to obtain the final product.
[0033] In a specific embodiment of the above method, the cobalt salt is selected from soluble cobalt salts, preferably inorganic cobalt salts such as cobalt nitrate, cobalt chloride or cobalt sulfate, and more preferably cobalt nitrate.
[0034] In a specific embodiment of the above method, the electrodeposition conditions are -0.8 to -1.2 V, 10-40 minutes; preferably -1 V, 20-30 minutes; more preferably -1 V, 20 minutes.
[0035] In a specific embodiment of the above method, the concentration of the selected cobalt salt is 0.8-1.5 mol / L, preferably 0.8-1.2 mol / L, more preferably 1 mol / L.
[0036] In step 3 of the specific implementation of the above method, the heating process conditions are: 200-500°C, 1-3 hours, preferably 300-500°C, 1-3 hours; more preferably 350°C, 400°C or 450°C, 2 hours.
[0037] The present application utilizes an electrodeposition method and a high-temperature calcination method to prepare the catalyst, and the synthesis process is simple and easy to scale up, thus having a higher application prospect.
[0038] In a third aspect, the present application provides the use of the yttrium-doped cobalt-based catalyst described in the first aspect or the yttrium-doped cobalt-based catalyst prepared by the preparation method described in the second aspect in the production of hydrogen and / or oxygen by decomposing water.
[0039] The unique nanosheet array structure of the catalyst of the present application gives it abundant geometric edge active sites, good hydrophilicity and mass transfer diffusion channels; the lower crystallinity is more conducive to the adsorption of water molecules and the transmission of electrons during the catalytic reaction, optimizes the electronic structure of the active sites, ensures the activity of the material while giving the material relatively excellent stability, and shows the phenomenon of increased activity in long-term stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 This is the X-ray diffraction pattern (XRD) of the products prepared in Comparative Example 1 and Example 1, Example 2, Example 3, Example 4, and Example 5.
[0041] Figure 2 These are low-magnification and high-magnification scanning electron microscope photographs (SEM) of the products prepared in Comparative Example 1 and Examples 1, 2, 3, 4 and 5.
[0042] Figure 3 This is the Raman spectra of the products prepared in Comparative Example 1 and Example 1, Example 2, Example 3, Example 4, and Example 5.
[0043] Figure 4 Polarization curves of the oxygen evolution reaction of the products prepared in Comparative Example 1 and Examples 1, 2, 3, 4 and 5 in 1 mol / L KOH solution.
[0044] Figure 5 Polarization curves of oxygen evolution reaction of the products prepared in Comparative Example 1 and Examples 1, 2, 3, 4 and 5 in 0.5 mol / L H2SO4 solution.
[0045] Figure 6 This is a chronopotentiostatic stability test graph of the oxygen evolution reaction of the products prepared in Comparative Example 1 and Examples 1, 2, 3, 4 and 5 in 1 mol / L KOH solution. DETAILED DESCRIPTION
[0046] The present application will be further described below through specific embodiments, but the scope of the present application is not limited thereto.
[0047] The ultrapure water used in the experiment was of conductivity 18.25 MΩ, and the reagents used in the experiment were of analytical grade.
[0048] Main instruments and reagents used:
[0049] The deionized water used in the experiment was ultrapure water with a conductivity of 18.25 MΩ, and the reagents used in the experiment were all analytical grade.
[0050] Main instruments and reagents used:
[0051] Bio-Logic (SP-150) electrochemical workstation for cyclic voltammetry, linear sweep voltammetry, and chronopotentiometry stability testing;
[0052] Milli-Q ultrapure water system (Merck Millipore, Germany) was used to prepare ultrapure water;
[0053] ME204 / 02 analytical balance (METTLER-TOLEDO Instrument Co., Ltd.) was used to weigh drugs;
[0054] MiniFlex diffractometer (Rigaku, Japan) was used for X-ray diffraction characterization;
[0055] Apreo S field emission scanning electron microscope (FEI, Thermo Fisher Scientific, USA) was used for catalyst morphology characterization;
[0056] A LabRAM HR Evolution Raman spectrometer (HORIBA Jobin Yvon SAS, France) was used for structural spectroscopic characterization of the catalysts;
[0057] DHG-9070A vacuum drying oven (Shanghai Yiheng Scientific Instrument Co., Ltd.);
[0058] SB-5200D ultrasonic cleaner (Ningbo Xinzhi Biotechnology Co., Ltd.);
[0059] PT-X platinum electrode clip, platinum sheet electrode, and Hg / HgO reference electrode (Wuhan Gaoshi Ruilian Technology Co., Ltd.) were used for electrochemical testing;
[0060] Cobalt nitrate (Beijing Inokai Technology Co., Ltd.);
[0061] Yttrium nitrate (Chengdu Kelong Chemical Co., Ltd.);
[0062] Potassium hydroxide (Chengdu Kelong Chemical Co., Ltd.);
[0063] Sulfuric acid (Guangzhou Donghong Chemical Plant);
[0064] Anhydrous ethanol (Lianlong Bohua Pharmaceutical Chemical Co., Ltd.);
[0065] Carbon cloth (Fuel Cell Store).
[0066] Comparative Example 1 Water splitting catalyst-carbon cloth / cobalt tetroxide preparation process
[0067] 1) Cut the carbon cloth (2×2cm 2 ) was placed in 50 mL of ethanol for ultrasonic cleaning for 15 minutes. After taking it out, it was rinsed alternately with ultrapure water and ethanol for several times. The rinsed carbon cloth was spread on the bottom of the beaker, a little ethanol was dropped, and then concentrated nitric acid was added until the carbon cloth was covered. After waiting for the reaction to be completed, it was rinsed several times with a large amount of ultrapure water (the above operations were all performed in a fume hood), and then ethanol and ultrapure water were repeatedly ultrasonically alternated for 15 minutes, and finally the treated carbon cloth was stored in ultrapure water for later use.
[0068] 2) Mix 29.03g of cobalt nitrate hexahydrate and 50mL of water in a 100mL beaker A and stir to dissolve. Pour the solution in beaker A into a 1000mL volumetric flask, add deionized water to make up the volume, and shake evenly to obtain a 0.1mol / LCo(NO3)3 solution.
[0069] 3) Take 60mL of 0.1mol / L Co(NO3)3 solution in beaker C, clamp the hydrophilic carbon cloth in the electrode clamp as the working electrode, the platinum electrode as the counter electrode, and Ag / AgCl as the reference electrode. Use Chenhua 760E workstation to apply -1V electrodeposition to the working electrode for 10-40 minutes. After the end, carefully rinse the carbon cloth material with deionized water and ethanol and dry it.
[0070] 4) The dried carbon obtained in step 3) is placed in a magnetic boat, placed in a high-temperature box furnace, heated to 350°C, maintained for 2 hours, and then cooled to obtain the final product, which is Co3O4. The heating rate is 5°C / min to 15°C / min, and the cooling rate is 100°C / h to 150°C / h.
[0071] The X-ray diffraction pattern of the product is Figure 1 As shown, high- and low-magnification electron microscope photos are Figure 2 As shown, the Raman spectrum is Figure 3 shown.
[0072] Example 1 Water splitting catalyst-carbon cloth / bulk yttrium doped cobalt tetroxide
[0073] 1) Cut the carbon cloth (2×2cm 2) was placed in 50 mL of ethanol for ultrasonic cleaning for 15 minutes. After taking it out, it was rinsed alternately with ultrapure water and ethanol for several times. The rinsed carbon cloth was spread on the bottom of the beaker, a little ethanol was dropped, and then concentrated nitric acid was added until the carbon cloth was covered. After waiting for the reaction to be completed, it was rinsed several times with a large amount of ultrapure water (the above operations were all performed in a fume hood), and then ethanol and ultrapure water were repeatedly ultrasonically alternated for 15 minutes, and finally the treated carbon cloth was stored in ultrapure water for later use.
[0074] 2) Mix 29.03g of cobalt nitrate hexahydrate and 50mL of water in a 100mL beaker A and stir to dissolve. Pour the solution in beaker A into a 1000mL volumetric flask, add deionized water to make up the volume, and shake evenly to obtain a 0.1mol / LCo(NO3)3 solution.
[0075] 3) Mix 38.30g of yttrium nitrate hexahydrate and 50mL of water in a 100mL beaker B and stir to dissolve. Pour the solution in beaker B into a 1000mL volumetric flask, add deionized water to make up to volume, and shake evenly to obtain a 0.1mol / LY(NO3)3 solution.
[0076] 4) Take 57mL 0.1mol / L Co(NO3)3 solution and 3mL 0.1mol / LY(NO3)3 solution in beaker C, clamp the hydrophilic carbon cloth in the electrode clamp as the working electrode, the platinum electrode as the counter electrode, and Ag / AgCl as the reference electrode. Use Chenhua 760E workstation to apply -1V electrodeposition to the working electrode for 20 minutes. After the end, carefully rinse the carbon cloth material with deionized water and ethanol and dry it.
[0077] 5) The dried carbon obtained in step 3) is placed in a magnetic boat, placed in a high-temperature box furnace, heated to 350°C, maintained for 2 hours, and then cooled to obtain the final product, which is calculated as 5% Y BULK -Co3O4 (yttrium bulk doping). The heating rate is 5°C / min to 15°C / min, and the cooling rate is 100°C / h to 150°C / h.
[0078] In this product, the doping amount of Y element is 5.3% based on the amount of Co substance. The loading amount of Y-Co3O4 on the carbon cloth is 0.875 mg / cm 2 .
[0079] The X-ray diffraction pattern of the product is as follows Figure 1 As shown, high- and low-magnification electron microscope photos are Figure 2 As shown, the Raman spectrum is Figure 3 shown.
[0080] from Figure 2 It can be seen that after yttrium doping, the product presents a nanoarray morphology with obvious curved edges.
[0081] Example 2 Water splitting catalyst-carbon cloth / surface yttrium doped cobalt tetroxide
[0082] 1) Cut the carbon cloth (2×2cm 2 ) was placed in 50 mL of ethanol for ultrasonic cleaning for 15 minutes. After taking it out, it was rinsed alternately with ultrapure water and ethanol for several times. The rinsed carbon cloth was spread on the bottom of the beaker, a little ethanol was dropped, and then concentrated nitric acid was added until the carbon cloth was covered. After waiting for the reaction to be completed, it was rinsed several times with a large amount of ultrapure water (the above operations were all performed in a fume hood), and then ethanol and ultrapure water were repeatedly ultrasonically alternated for 15 minutes, and finally the treated carbon cloth was stored in ultrapure water for later use.
[0083] 2) Mix 29.03g of cobalt nitrate hexahydrate and 50mL of water in a 100mL beaker A and stir to dissolve. Pour the solution in beaker A into a 1000mL volumetric flask, add deionized water to make up the volume, and shake evenly to obtain a 0.1mol / LCo(NO3)3 solution.
[0084] 3) Mix 38.30g of yttrium nitrate hexahydrate and 50mL of water in a 100mL beaker B and stir to dissolve. Pour the solution in beaker B into a 1000mL volumetric flask, add deionized water to make up to volume, and shake evenly to obtain a 0.1mol / LY(NO3)3 solution.
[0085] 4) Take 57mL 0.1mol / L Co(NO3)3 solution and 3mL 0.1mol / LY(NO3)3 solution in beaker C, clamp the hydrophilic carbon cloth in the electrode clamp as the working electrode, the platinum electrode as the counter electrode, and Ag / AgCl as the reference electrode. Use Chenhua 760E workstation to apply -1V electrodeposition to the working electrode for 20 minutes. After the end, carefully rinse the carbon cloth material with deionized water and ethanol and dry it.
[0086] 5) The dried carbon cloth obtained in step 4) was clamped in the electrode clamp as the working electrode, the platinum electrode sheet was used as the counter electrode, Ag / AgCl was used as the reference electrode, and the electrolyte was the same as step 4), 57mL 0.1mol / L Co(NO3)3 and 3mL 0.1mol / LY(NO3)3 solution. The working electrode was subjected to 20 cycles of cyclic voltammetry current using the Chenhua 760E workstation, with a voltage range of -1V to 1V, and 20 cycles of electrodeposition. After completion, the carbon cloth material was carefully rinsed with deionized water and ethanol and dried.
[0087] 6) The dried carbon obtained in step 5) is placed in a magnetic boat, placed in a high-temperature box furnace, heated to 350°C, maintained for 2 hours, and then cooled to obtain the final product, which is calculated as 5% Y SUP-Co3O4 (yttrium surface doping). The heating rate is 5°C / min to 15°C / min, and the cooling rate is 100°C / h to 150°C / h.
[0088] In this product, the doping amount of Y element is 4.6% based on the amount of Co substance. The loading amount of Y-Co3O4 on the carbon cloth is 0.75 mg / cm 2 .
[0089] The X-ray diffraction pattern of the product is as follows Figure 1 As shown, high- and low-magnification electron microscope photos are Figure 2 As shown, the Raman spectrum is Figure 3 shown.
[0090] Example 3 Water splitting catalyst-carbon cloth / bulk yttrium doped cobalt tetroxide
[0091] 1) Cut the carbon cloth (2×2cm 2 ) was placed in 50 mL of ethanol for ultrasonic cleaning for 15 minutes. After taking it out, it was rinsed alternately with ultrapure water and ethanol for several times. The rinsed carbon cloth was spread on the bottom of the beaker, a little ethanol was dropped, and then concentrated nitric acid was added until the carbon cloth was covered. After waiting for the reaction to be completed, it was rinsed several times with a large amount of ultrapure water (the above operations were all performed in a fume hood), and then ethanol and ultrapure water were repeatedly ultrasonically alternated for 15 minutes, and finally the treated carbon cloth was stored in ultrapure water for later use.
[0092] 2) Mix 29.03g of cobalt nitrate hexahydrate and 50mL of water in a 100mL beaker A and stir to dissolve. Pour the solution in beaker A into a 1000mL volumetric flask, add deionized water to make up the volume, and shake evenly to obtain a 0.1mol / LCo(NO3)3 solution.
[0093] 3) Mix 38.30g of yttrium nitrate hexahydrate and 50mL of water in a 100mL beaker B and stir to dissolve. Pour the solution in beaker B into a 1000mL volumetric flask, add deionized water to make up to volume, and shake evenly to obtain a 0.1mol / LY(NO3)3 solution.
[0094] 4) Take 58.8mL 0.1mol / L Co(NO3)3 solution and 1.2mL 0.1mol / LY(NO3)3 in beaker C, clamp the hydrophilic carbon cloth in the electrode clamp as the working electrode, the platinum electrode as the counter electrode, and Ag / AgCl as the reference electrode. Use Chenhua 760E workstation to apply -1V electrochemical precipitation to the working electrode for 20 minutes. After the end, carefully rinse the carbon cloth material with deionized water and ethanol and dry it.
[0095] 5) The dried carbon obtained in step 3) is placed in a magnetic boat, loaded into a high-temperature box furnace, heated to 350°C, maintained for 2 hours, and then cooled to obtain the final product, which is 2% Y-Co3O4 (yttrium bulk phase doping).
[0096] In this product, the doping amount of Y element is 1.3% based on the amount of Co substance. The loading amount of Y-Co3O4 on the carbon cloth is 0.33 mg / cm 2 .
[0097] The X-ray diffraction pattern of the product is as follows Figure 1 As shown, high- and low-magnification electron microscope photos are Figure 2 As shown, the Raman spectrum is Figure 3 shown.
[0098] Example 4 Water splitting catalyst-carbon cloth / bulk yttrium doped cobalt tetroxide
[0099] 1) Cut the carbon cloth (2×2cm 2 ) was placed in 50 mL of ethanol for ultrasonic cleaning for 15 minutes. After taking it out, it was rinsed alternately with ultrapure water and ethanol for several times. The rinsed carbon cloth was spread on the bottom of the beaker, a little ethanol was dropped, and then concentrated nitric acid was added until the carbon cloth was covered. After waiting for the reaction to be completed, it was rinsed several times with a large amount of ultrapure water (the above operations were all performed in a fume hood), and then ethanol and ultrapure water were repeatedly ultrasonically alternated for 15 minutes, and finally the treated carbon cloth was stored in ultrapure water for later use.
[0100] 2) Mix 29.03g of cobalt nitrate hexahydrate and 50mL of water in a 100mL beaker A and stir to dissolve. Pour the solution in beaker A into a 1000mL volumetric flask, add deionized water to make up the volume, and shake evenly to obtain a 0.1mol / LCo(NO3)3 solution.
[0101] 3) Mix 38.30g of yttrium nitrate hexahydrate and 50mL of water in a 100mL beaker B and stir to dissolve. Pour the solution in beaker B into a 1000mL volumetric flask, add deionized water to make up to volume, and shake evenly to obtain a 0.1mol / LY(NO3)3 solution.
[0102] 4) Take 55.2mL 0.1mol / L Co(NO3)3 solution and 4.8mL 0.1mol / LY(NO3)3 solution in beaker C, clamp the hydrophilic carbon cloth in the electrode clamp as the working electrode, the platinum electrode as the counter electrode, and Ag / AgCl as the reference electrode. Use Chenhua 760E workstation to apply -1V electrodeposition to the working electrode for 20 minutes. After the end, carefully rinse the carbon cloth material with deionized water and ethanol and dry it.
[0103] 5) The dried carbon obtained in step 3) is placed in a magnetic boat, placed in a high temperature box furnace, heated to 350°C, maintained for 2 hours, and then cooled to obtain a final product, which is 8% Y-Co3O4 (yttrium bulk doped). The heating rate is 5°C / min to 15°C / min, and the cooling rate is 100°C / h to 150°C / h.
[0104] In this product, the doping amount of Y element is 6.4% based on Co. The loading amount of Y-Co3O4 on the carbon cloth is 1.30 mg / cm 2 .
[0105] The X-ray diffraction pattern of the product is as follows Figure 1 As shown, high- and low-magnification electron microscope photos are Figure 2 As shown, the Raman spectrum is Figure 3 shown.
[0106] Example 5 Water splitting catalyst-carbon cloth / bulk yttrium doped cobalt tetroxide
[0107] 1) Cut the carbon cloth (2×2cm 2 ) was placed in 50 mL of ethanol for ultrasonic cleaning for 15 minutes. After taking it out, it was rinsed alternately with ultrapure water and ethanol for several times. The rinsed carbon cloth was spread on the bottom of the beaker, a little ethanol was dropped, and then concentrated nitric acid was added until the carbon cloth was covered. After waiting for the reaction to be completed, it was rinsed several times with a large amount of ultrapure water (the above operations were all performed in a fume hood), and then ethanol and ultrapure water were repeatedly ultrasonically alternated for 15 minutes, and finally the treated carbon cloth was stored in ultrapure water for later use.
[0108] 2) Mix 29.03g of cobalt nitrate hexahydrate and 50mL of water in a 100mL beaker A and stir to dissolve. Pour the solution in beaker A into a 1000mL volumetric flask, add deionized water to make up the volume, and shake evenly to obtain a 0.1mol / LCo(NO3)3 solution.
[0109] 3) Mix 38.30g of yttrium nitrate hexahydrate and 50mL of water in a 100mL beaker B and stir to dissolve. Pour the solution in beaker B into a 1000mL volumetric flask, add deionized water to make up to volume, and shake evenly to obtain a 0.1mol / LY(NO3)3 solution.
[0110] 4) Take 52.2mL 0.1mol / L Co(NO3)3 solution and 7.8mL 0.1mol / LY(NO3)3 solution in beaker C, clamp the hydrophilic carbon cloth in the electrode clamp as the working electrode, the platinum electrode as the counter electrode, and Ag / AgCl as the reference electrode. Use Chenhua 760E workstation to apply -1V electrodeposition to the working electrode for 20 minutes. After the end, carefully rinse the carbon cloth material with deionized water and ethanol and dry it.
[0111] 5) The dried carbon obtained in step 3) is placed in a magnetic boat, placed in a high temperature box furnace, heated to 350°C, maintained for 2 hours, and then cooled to obtain a final product, which is 13% Y-Co3O4 (yttrium bulk doped). The heating rate is 5°C / min to 15°C / min, and the cooling rate is 100°C / h to 150°C / h.
[0112] In this product, the doping amount of Y element is 11.5% based on Co. The loading amount of Y-Co3O4 on the carbon cloth is 2.12 mg / cm 2 .
[0113] The X-ray diffraction pattern of the product is as follows Figure 1 As shown, high- and low-magnification electron microscope photos are Figure 2 As shown, the Raman spectrum is Figure 3 shown.
[0114] Test Example 1
[0115] The catalyst products obtained in the examples and comparative examples were cut into 0.5×2 cm 2 The working electrode was directly clamped on the Pt electrode clamp, the platinum electrode was used as the counter electrode, and the Hg / HgO electrode was used as the reference electrode. The oxygen evolution reaction test was carried out in a 1 mol / L KOH solution using a three-electrode system. The test method used cyclic voltammetry with a scan rate of 5 mV / s to obtain the corresponding polarization curve, as shown in the figure. Figure 4 shown.
[0116] from Figure 4 It can be seen that the product catalyst 10mA / cm 2 The overpotential of the water decomposition current density is 340 mV. The product catalyst obtained in Example 1 has a current density of 10 mA / cm 2 The overpotential of the water decomposition current density is only 240 mV. The product catalyst obtained in Example 2 has a current density of 10 mA / cm 2 The overpotential of the water decomposition current density is 280 mV. The product catalyst obtained in Example 3 has a current density of 10 mA / cm 2 The overpotential of the water decomposition current density is 283 mV. The product catalyst obtained in Example 4 has a current density of 10 mA / cm 2 The overpotential of the water decomposition current density is 283 mV. The product catalyst obtained in Example 5 has a current density of 10 mA / cm 2 The overpotential for the water splitting current density is 283 mV.
[0117] Test Example 2
[0118] The catalyst products obtained in the examples and comparative examples were cut into 0.5×2 cm2 The working electrode was directly clamped on the Pt electrode clamp, the platinum electrode was used as the counter electrode, and the HgSO4 electrode was used as the reference electrode. The oxygen evolution reaction test was carried out in a 0.5 mol / L H2SO4 solution using a three-electrode system. The test method used cyclic voltammetry with a scan rate of 5 mV / s to obtain the corresponding polarization curve, as shown in the figure. Figure 5 shown.
[0119] from Figure 5 It can be seen that the product catalyst 10mA / cm 2 The overpotential of the water decomposition current density is 345 mV. The product catalyst obtained in Example 1 has a current density of 10 mA / cm 2 The overpotential of the water decomposition current density is only 280 mV. The product catalyst obtained in Example 2 has a current density of 10 mA / cm 2 The overpotential of the water decomposition current density is 333 mV. The product catalyst obtained in Example 3 has a current density of 10 mA / cm 2 The overpotential of the water decomposition current density is 285 mV. The product catalyst obtained in Example 4 has a current density of 10 mA / cm 2 The overpotential of the water decomposition current density is 283 mV. The product catalyst obtained in Example 5 has a current density of 10 mA / cm 2 The overpotential of the water splitting current density is 288 mV.
[0120] Test Example 3
[0121] The catalyst products obtained in the examples and comparative examples were cut into 0.5×2 cm 2 The working electrode was directly clamped on the Pt electrode clamp, the platinum electrode was used as the counter electrode, and the Hg / HgO electrode was used as the reference electrode. The oxygen evolution reaction stability test was carried out in 1 mol / L KOH solution using a three-electrode system. The test method was chronopotentiometry, such as Figure 6 shown.
[0122] from Figure 6 It can be seen that the product catalysts obtained in Comparative Example 1, Example 1 and Example 2 maintained good alkaline stability within 20 hours. The catalytic potential of the product catalysts obtained in Example 3, Example 4 and Example 5 gradually increased during the entire test process, and the material stability gradually deteriorated.
[0123] Finally, it should be noted that the above is only a preferred embodiment of the present application and is not intended to limit the present application. Although the present application is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principles of the present application shall be included in the protection scope of the present application.
Claims
1. A yttrium-doped cobalt-based catalyst, comprising a substrate and a composite material supported on the substrate, wherein the composite material comprises cobalt oxide and yttrium-doped cobalt oxide.
2. The catalyst according to claim 1, characterized in that Based on the total molar amount of cobalt oxide and yttrium-doped cobalt oxide, the molar content of the yttrium element is 1%-15%, preferably 3%-10%, and more preferably 4%-8%.
3. The catalyst according to claim 1 or 2, characterized in that The cobalt oxide is cobalt tetroxide, and the yttrium-doped cobalt oxide is yttrium-doped cobalt tetroxide. Preferably, the doping is bulk doping and / or surface doping.
4. The catalyst according to any one of claims 1 to 3, characterized in that The composite material is a composite material composed of a plurality of nanosheets, wherein the nanosheets include cobalt oxide and yttrium-doped cobalt oxide.
5. The catalyst according to any one of claims 1 to 4, characterized in that The loading amount of the composite material on the substrate is 0.3 mg / cm 2 -2.5mg / cm 2 , preferably 0.5 mg / cm 2 -1.5mg / cm 2 More preferably 0.5 mg / cm 2 -1.0mg / cm 2 ; and / or The substrate is selected from one or more conductive substrates, preferably one or more carbon cloth, graphite sheet, nickel mesh and nickel foam.
6. A method for preparing a yttrium-doped cobalt-based catalyst, comprising the following steps: S1: immersing the substrate in a solution containing a yttrium source and a cobalt source for electrochemical deposition to obtain a precursor containing cobalt oxyhydroxide; S2: heat-treating the precursor of step S1 to obtain the yttrium-doped cobalt-based catalyst.
7. The preparation method according to claim 6, characterized in that: Calculated in terms of yttrium element and cobalt element, the molar ratio of the yttrium source to the cobalt source is 1:5-1:50, preferably 1:10-1:30, more preferably 1:15-1:25, for example 1:18-1:
22.
8. The preparation method according to claim 6 or 7, characterized in that: In step S1, the potential of the electrochemical deposition is -0.4V to -1.6V, preferably -0.8V to -1.2V, and / or the time of the electrochemical deposition is 5min to 60min, preferably 10min to 40min; and / or In step S2, the temperature of the heat treatment is 200°C-500°C, preferably 300°C-500°C, and / or the time of the heat treatment is 0.5h-5h, preferably 1h-3h.
9. The preparation method according to any one of claims 6 to 8, characterized in that: The yttrium source is selected from one or more soluble yttrium salts, preferably one or more yttrium nitrate, yttrium sulfate, yttrium acetate and yttrium chloride; and / or The cobalt source is selected from one or more soluble cobalt salts, preferably one or more cobalt nitrate, cobalt sulfate, cobalt acetate and cobalt chloride; and / or The substrate is selected from one or more conductive substrates, preferably one or more carbon cloth, graphite sheet, nickel mesh and nickel foam.
10. Use of the yttrium-doped cobalt-based catalyst according to any one of claims 1 to 5 or the yttrium-doped cobalt-based catalyst prepared by the preparation method according to any one of claims 6 to 9 in the production of hydrogen and / or oxygen by decomposing water.
Citation Information
Cited By
Electrode material based on rare earth doping and preparation method thereof
CN121076159A